STUDI KOMPARASI PENERAPAN METODE ACTIVE LEARNING MODEL READING ALOUD DAN METODE KONVENSIONAL MODEL CERAMAH DALAM PEMBELAJARAN BAHASA ARAB DAN PENGARUHNYA TERHADAP RESPON SISWA KELAS V MI MA’ARIF 01 PAHONJEAN MAJENANG - Hasanah, Siti Uswatun (Jurnal Tawadhu, 2019)
This study aims to find out how the application of active learning methods of reading aloud models and conventional methods of lecture models in learning Arabic and their influence on learning outcomes of fifth grade students in MI Ma'arif 01 Pahonjean. With this research, it is expected to provide new input to all parties involved in the world of education in general and Arabic Language Education in particular. In connection with the theme of the adopted writer, the authors hope to know the learning model with the application of active learning methods aloud reading models and conventional methods of modeling lecture in the teaching-learning process, so that the application can create a spirit of learning, the creation of student motivation, and can compare between the two methods.This research is a quantitative descriptive research by taking the object of research in MI Ma'arif 01 Pahonjean. Data collection is done by interviews, questionnaires, and documentation. The sample of this study was class V. Data on student results were analyzed using the Independent Sample Test and questionnaire responses of students were analyzed using descriptive analysis.Based on the results of the study it can be concluded that: (1) There is no difference between the classes using the active learning method aloud reading model and the conventional method of lecture model with a significance level of P <0.05; (2) there are differences there are differences in responses from class V students of MI Ma'arif 01 Pahonjean regarding the two methods, with an average percentage of active learning methods reading aloud model of 79.8% and the average percentage of conventional methods of lecture models of 54%.